A method for preparing a corrosion-resistant basalt fiber-reinforced photovoltaic module
Through the molding and curing forming method of modified basalt fiber fabrics and vinyl ester resins, the problem of poor mechanical properties of photovoltaic module composite materials is solved, and the corrosion resistance and mechanical strength of the material are significantly improved.
Patent Information
- Application Number
- CN202411096255.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The bending strength and impact strength of existing photovoltaic module composite materials are relatively low and have poor mechanical properties.
The modified basalt fiber fabric is formed by soaking the basalt fiber fabric in ethanol and adding chemical substances such as 3-mercaptopropyltriethoxysilane and epoxycyclohexyl-cage polysilsesquioxane, and then molding and curing with vinyl ester resin to prepare anti-corrosion basalt reinforced composite fibers.
It significantly improves the corrosion resistance and mechanical strength of the fibers, and improves the overall performance of the composite material, including bending strength and impact strength.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic module materials, in particular to a method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module. Background Art
[0002] Photovoltaic module is a device that converts solar energy into electrical energy. It is mostly used in situations where solar power generation is used, such as solar power plants, solar street lights, etc.
[0003] Basalt fiber is an environmentally friendly fiber with excellent performance. It is made of pure natural basalt ore as raw material, melted at 1450-1500℃, and made by platinum-rhodium alloy wire drawing process. As an inorganic high-performance fiber, basalt fiber has the advantages of high strength and high modulus, high and low temperature resistance, acid and alkali corrosion resistance, and good creep resistance, so it can replace expensive carbon fiber and aramid fiber as a reinforcement for composite materials.
[0004] Chinese patent CN112189264A: relates to a lightweight photovoltaic module (1), comprising: a first transparent layer (2) forming a front surface, a photovoltaic cell (4), a component (3) for encapsulating the photovoltaic cell (4), and a second layer (5), wherein the encapsulation component (3) and the photovoltaic cell (4) are arranged between the first layer (2) and the second layer (5). The invention is characterized in that the first layer (2) comprises a polymer material and has a thickness (e2) of less than 50 μm; and the second layer (5) comprises at least one composite material of the prepreg type comprising a polymer resin and fibers, and the weight per unit area thereof is less than 150 g / m 2 , and the packaging component (3) has a maximum thickness (e3) less than 150 μm.
[0005] Chinese patent CN118120063A: Mainly relates to a photovoltaic module (1) obtained by stacking, the stacking comprising: a first transparent layer (2) forming the front; a plurality of photovoltaic cells (4); a component (3) encapsulating the plurality of cells (4); and a second layer (5) forming the back. The first layer (2) comprises: a front layer (2a) made of at least one polymer material; at least one front component (2b, 2c) comprising an interface front layer (2b) and a glass front layer (2c), the thickness of the glass front layer (2c) being less than or equal to 2 mm, the at least one front component (2b, 2c) being located between the polymer front layer (2a) and the encapsulation component (3), and the interface front layer (2b, 2c) of the at least one front component (2b, 2c) being located between the polymer front layer (2a) and the glass front layer (2c).
[0006] Chinese patent CN115336009A: relates to a photovoltaic module, which comprises a protective front layer element, an encapsulation layer element, a photovoltaic cell element and a protective back layer element, wherein at least one of the protective elements comprises glass; wherein the encapsulation layer element comprises a polymer composition (I), wherein the polymer composition (I) comprises at least the following components: (A) 97.00 to 99.99% by weight of a polymer selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a) based on the total weight of the polymer composition (I), wherein the ethylene polymer (a) is selected from (a1) ethylene copolymers with functional group-containing units; (a2) one or more monomer units selected from (C1-C6)-alkyl acrylates or (C1-C6)-alkyl acrylates. (a3) an ethylene copolymer containing one or more α-olefin comonomer units; and optionally with functional group-containing units different from the one or more polar comonomer units of polymer (a2); or a mixture thereof; and (b) units containing one or more silane groups; (B) 0.01 to 3.00 wt. % of a compound according to formula (I) based on the total weight of the polymer composition (I); wherein: R1, R1', R2 and R2' are each independently selected from the group consisting of hydrogen, n-alkyl, isoalkyl, alkoxy, cycloalkyl, alkenyl, halogen and mixtures thereof; X is selected from the group consisting of primary amines, secondary amines, tertiary amines, hydrogen, alkyl, alkenyl and mixtures thereof.
[0007] However, the composite materials prepared by the above patents and prior art have technical defects of low bending strength and impact strength and poor mechanical properties. Summary of the invention
[0008] The present invention provides a method for preparing a corrosion-resistant basalt fiber reinforced photovoltaic module to solve at least one technical problem in the above-mentioned background technology.
[0009] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0010] S1: Soak 110-150 parts of basalt fiber fabric in 1000-1200 parts of ethanol for 20-30 hours to remove the surface sizing agent; then add 5-8 parts of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6, and react at 60-70°C for 60-100 minutes;
[0011] S2: Add 0.02-0.3 parts of epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.005-0.07 parts of 2-amino-5-chloro-2'-fluorobenzophenone, 0.003-0.05 parts of perfluoropolyether (meth)acrylate, and 2-5 parts of sodium ethoxide, react at 60-70° C. for 100-150 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0012] S3: Six layers of modified basalt fiber fabric and 20-30 parts of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber.
[0013] According to the method provided by the present invention, the photovoltaic module includes a transparent plate, a back plate, a photovoltaic cell, and a support.
[0014] According to the method provided by the present invention, the photovoltaic cell is sealed between the transparent plate and the back plate.
[0015] According to the method provided by the present invention, the support member is fixed on the photovoltaic backboard.
[0016] According to the method provided by the present invention, the anti-corrosion basalt reinforced composite fiber is applied to photovoltaic module materials.
[0017] According to the method provided by the present invention, the basalt fiber fabric has a plain weave structure, a warp and weft density of 40-50 strands / 10cm, and a surface density of 250-300g / m 2 .
[0018] According to the method provided by the present invention, the average molecular weight of the perfluoropolyether (meth)acrylate is 1000-4000.
[0019] According to the method provided by the present invention, the molding curing conditions are: 25-30°C, time 30-60min, pressure 2-5Mpa, and composite material thickness 1-3mm.
[0020] Reaction mechanism
[0021] 1. The basalt fiber fabric treated with 3-mercaptopropyltriethoxysilane undergoes a mercapto-epoxy point reaction with epoxycyclohexyl-cage polysilsesquioxane
[0022] Reaction mechanism: The mercapto group (-SH) contained in 3-mercaptopropyltriethoxysilane undergoes a ring-opening reaction with the epoxy group (-CH(O)CH-) in epoxycyclohexyl-cage polysilsesquioxane to form a stable thioethylene glycol structure; the epoxy group is easily attacked by nucleophilic reagents such as mercapto due to the tension and polarity of its three-membered ring, resulting in ring cleavage and the formation of addition products; this process usually requires an alkaline catalyst to promote the deprotonation of the mercapto group and enhance its nucleophilicity.
[0023] 2. Amino-epoxy reaction of 2-amino-5-chloro-2'-fluorobenzophenone with epoxycyclohexyl-cage polysilsesquioxane
[0024] Reaction mechanism: The amino group (-NH2) in 2-amino-5-chloro-2'-fluorobenzophenone acts as a nucleophile to attack the epoxy group in epoxycyclohexyl-cage polysilsesquioxane, undergoing a ring-opening reaction to generate the corresponding β-hydroxylamine compound; the lone pair of electrons of the amino group attacks the electropositive carbon atom in the epoxy group, causing the ring to break and form a new CN bond and hydroxyl group.
[0025] Technical Effects
[0026] The present invention discloses a method for preparing a corrosion-resistant basalt fiber reinforced photovoltaic module. Compared with the prior art, the present invention has the following significant effects:
[0027] 1. Through the mercapto-epoxy point reaction, a uniform and continuous siloxane film can be formed on the surface of basalt fiber, which significantly improves the corrosion resistance and mechanical strength of the fiber; the modified fiber shows better interface compatibility and mechanical properties in the composite material, which helps to improve the overall performance of the composite material.
[0028] 2. The introduction of 2-amino-5-chloro-2'-fluorobenzophenone can effectively improve the thermal stability and chemical stability of the material through amino-epoxy reaction; this reaction not only improves the cross-linking density of the composite material, but also enhances the application performance of the material in harsh environments by introducing chemical-resistant functional groups.
[0029] The above two reaction mechanisms and their technical effects provide a scientific basis and experimental guidance for the preparation of high-performance, functionalized basalt fiber-reinforced composites, significantly enhancing their application potential in corrosion resistance and weather resistance. DETAILED DESCRIPTION
[0030] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples:
[0031] Example 1
[0032] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0033] S1: Soak 110g of basalt fiber fabric in 1000g of ethanol for 20h to remove the surface sizing agent; then add 5g of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6 and react at 60℃ for 60 minutes;
[0034] S2: Add 0.02 g epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.005 g 2-amino-5-chloro-2'-fluorobenzophenone, 0.003 g perfluoropolyether (meth)acrylate, and 2 g sodium ethoxide, react at 60° C. for 100 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0035] S3: 6 layers of modified basalt fiber fabric and 20 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0036] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0037] The basalt fiber fabric has a plain weave, with a warp and weft density of 40 threads / 10 cm and a surface density of 250 g / m 2 .
[0038] The average molecular weight of the perfluoropolyether (meth)acrylate is 1000.
[0039] The molding curing conditions are: 25° C., time 30 min, pressure 2 MPa, and composite material thickness 1 mm.
[0040] Example 2
[0041] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0042] S1: Soak 120g of basalt fiber fabric in 1050g of ethanol for 23h to remove the surface sizing agent; then add 6g of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6 and react at 65℃ for 70 minutes;
[0043] S2: Add 0.1 g epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.02 g 2-amino-5-chloro-2'-fluorobenzophenone, 0.02 g perfluoropolyether (meth)acrylate, and 3 g sodium ethoxide, react at 65° C. for 110 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0044] S3: 6 layers of modified basalt fiber fabric and 23 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0045] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0046] The basalt fiber fabric is plain weave with a warp and weft density of 45 threads / 10cm and a surface density of 260g / m 2 .
[0047] The average molecular weight of the perfluoropolyether (meth)acrylate is 2000.
[0048] The molding curing conditions are: 26° C., time 40 min, pressure 3 Mpa, and composite material thickness 2 mm.
[0049] Example 3
[0050] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0051] S1: Soak 140g of basalt fiber fabric in 1150g of ethanol for 28h to remove the surface sizing agent; then add 7g of 3-mercaptopropyltriethoxysilane CAS#: 14814-09-6 and react at 65°C for 90 minutes;
[0052] S2: Add 0.2 g epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.06 g 2-amino-5-chloro-2'-fluorobenzophenone, 0.04 g perfluoropolyether (meth)acrylate, and 4 g sodium ethoxide, react at 65° C. for 140 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0053] S3: 6 layers of modified basalt fiber fabric and 28 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0054] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0055] The basalt fiber fabric is plain weave with a warp and weft density of 45 threads / 10cm and a surface density of 280g / m 2 .
[0056] The average molecular weight of the perfluoropolyether (meth)acrylate is 3000.
[0057] The molding curing conditions are: 28° C., time 50 min, pressure 4 MPa, and composite material thickness 2 mm.
[0058] Example 4
[0059] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0060] S1: Soak 150g of basalt fiber fabric in 1200g of ethanol for 30h to remove the surface sizing agent; then add 8g of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6 and react at 70℃ for 100 minutes;
[0061] S2: Add 0.3 g epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.07 g 2-amino-5-chloro-2'-fluorobenzophenone, 0.05 g perfluoropolyether (meth)acrylate, and 5 g sodium ethoxide, react at 70° C. for 150 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0062] S3: 6 layers of modified basalt fiber fabric and 30 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0063] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0064] The basalt fiber fabric has a plain weave, with a warp and weft density of 50 strands / 10 cm and a surface density of 300 g / m 2 .
[0065] The average molecular weight of the perfluoropolyether (meth)acrylate is 4000.
[0066] The molding curing conditions are: 30° C., time 60 min, pressure 5 MPa, and composite material thickness 3 mm.
[0067] Comparative Example 1
[0068] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0069] S1: Soak 110 g of basalt fiber fabric in 1000 g of ethanol for 20 h to remove the surface sizing agent, and react at 60 ° C for 60 minutes;
[0070] S2: Add 0.02 g epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.005 g 2-amino-5-chloro-2'-fluorobenzophenone, 0.003 g perfluoropolyether (meth)acrylate, and 2 g sodium ethoxide, react at 60° C. for 100 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0071] S3: 6 layers of modified basalt fiber fabric and 20 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0072] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0073] The basalt fiber fabric has a plain weave, with a warp and weft density of 40 threads / 10 cm and a surface density of 250 g / m 2 .
[0074] The average molecular weight of the perfluoropolyether (meth)acrylate is 1000.
[0075] The molding curing conditions are: 25° C., time 30 min, pressure 2 MPa, and composite material thickness 1 mm.
[0076] Comparative Example 2
[0077] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0078] S1: Soak 110g of basalt fiber fabric in 1000g of ethanol for 20h to remove the surface sizing agent; then add 5g of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6 and react at 60℃ for 60 minutes;
[0079] S2: Add 0.005 g of 2-amino-5-chloro-2'-fluorobenzophenone, 0.003 g of perfluoropolyether (meth)acrylate, and 2 g of sodium ethoxide, react at 60° C. for 100 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0080] S3: 6 layers of modified basalt fiber fabric and 20 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0081] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0082] The basalt fiber fabric has a plain weave, with a warp and weft density of 40 threads / 10 cm and a surface density of 250 g / m 2 .
[0083] The average molecular weight of the perfluoropolyether (meth)acrylate is 1000.
[0084] The molding curing conditions are: 25° C., time 30 min, pressure 2 MPa, and composite material thickness 1 mm.
[0085] Comparative Example 3
[0086] A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0087] S1: Soak 110g of basalt fiber fabric in 1000g of ethanol for 20h to remove the surface sizing agent; then add 5g of 3-mercaptopropyltriethoxysilane CAS#:14814-09-6 and react at 60℃ for 60 minutes;
[0088] S2: Add 0.02 g of epoxycyclohexyl-cage polysilsesquioxane 187333-74-0, 0.003 g of perfluoropolyether (meth)acrylate, and 2 g of sodium ethoxide, react at 60° C. for 100 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric;
[0089] S3: 6 layers of modified basalt fiber fabric and 20 g of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber;
[0090] The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
[0091] The basalt fiber fabric has a plain weave, with a warp and weft density of 40 threads / 10 cm and a surface density of 250 g / m 2 .
[0092] The average molecular weight of the perfluoropolyether (meth)acrylate is 1000.
[0093] The molding curing conditions are: 25° C., time 30 min, pressure 2 MPa, and composite material thickness 1 mm.
[0094] Test and Evaluation:
[0095] 1. Bending strength: tested using a universal testing machine with a loading speed of 5mm / min;
[0096] 2. Impact strength: tested using a universal testing machine, the impact speed at the moment of contact with the sample is 5m / s;
[0097] 3. Corrosion resistance test: The anti-corrosion basalt reinforced composite fibers prepared in the examples and comparative examples were immersed in 8 wt % NaOH solution for 20 days, and their surfaces were observed.
[0098] Test results:
[0099] Bending strength / Mpa Impact strength / Mpa Corrosion resistance Example 1 299 159 No surface changes Example 2 306 163 No surface changes Example 3 317 165 No surface changes Example 4 321 168 No surface changes Comparative Example 1 234 122 Surface peeling Comparative Example 2 255 131 Surface cracks Comparative Example 3 263 136 Surface cracks
[0100] Through the data analysis of the above embodiments and comparative examples, the anti-corrosion basalt reinforced composite fiber prepared by the present invention has excellent mechanical properties and corrosion resistance.
[0101] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an anti-corrosion basalt fiber reinforced photovoltaic module, the operating steps of which are: S1: Soak 110-150 parts of basalt fiber fabric in 1000-1200 parts of ethanol for 20-30 hours to remove the surface sizing agent; then add 5-8 parts of 3-mercaptopropyltriethoxysilane and react at 60-70°C for 60-100 minutes; S2: Add 0.02-0.3 parts of epoxycyclohexyl-cage polysilsesquioxane, 0.005-0.07 parts of 2-amino-5-chloro-2'-fluorobenzophenone, 0.003-0.05 parts of perfluoropolyether (meth)acrylate, and 2-5 parts of sodium ethoxide, react at 60-70° C. for 100-150 minutes, take out, wash with anhydrous ethanol, and dry to obtain a modified basalt fiber fabric; S3: 6 layers of modified basalt fiber fabric and 20-30 parts of vinyl ester resin are molded and cured by a semi-automatic flat plate vulcanizer to obtain an anti-corrosion basalt reinforced composite fiber; The photovoltaic module comprises a transparent plate, a back plate, a photovoltaic cell, and a support member; the photovoltaic cell is sealed between the transparent plate and the back plate; the support member is fixed on the photovoltaic back plate; and the anti-corrosion basalt reinforced composite fiber is applied to the photovoltaic module material.
2. The method for preparing a corrosion-resistant basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The basalt fiber fabric has a plain weave, with a warp and weft density of 40-50 strands / 10cm and a surface density of 250-300g / m 2 .
3. The method for preparing a corrosion-resistant basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The average molecular weight of the perfluoropolyether (meth)acrylate is 1000-4000.
4. The method for preparing a corrosion-resistant basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The molding curing conditions are as follows: temperature of 25-30°C, time of 30-60min, pressure of 2-5Mpa, and thickness of the composite material of 1-3mm.
Citation Information
Patent Citations
Lightweight and flexible photovoltaic module comprising a front layer consisting of a polymer and a rear layer consisting of a composite material
CN112189264A
Photovoltaic module with enhanced resistance to potential induced degradation
CN115336009A
Lightweight photovoltaic module comprising glass and polymeric front layer
CN118120063A
High-temperature-resistant thermal aging basalt fiber-reinforced PBT (Polybutylene Terephthalate) composite material and preparation method thereof
CN103923442A
Graphene / cage-type polysilsesquioxane modified polyester fiber and preparation method
CN110093680A